2009
DOI: 10.1097/ccm.0b013e3181926430
|View full text |Cite
|
Sign up to set email alerts
|

Families with limited English proficiency receive less information and support in interpreted intensive care unit family conferences*

Abstract: Objective-Family communication is important for delivering high quality end-of-life care in the ICU, yet little research has been conducted to describe and evaluate clinician-family communication with non-English speaking family members. We assessed clinician-family communication during ICU family conferences involving interpreters and compared it to conferences without interpreters.Design-Cross-sectional descriptive study.Setting-Family conferences in the ICU's of four hospitals during which discussions about… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
70
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(71 citation statements)
references
References 28 publications
1
70
0
Order By: Relevance
“…29 Evaluation of communications between patients' families and health care providers during interpreted conferences revealed that alterations occurred 55% of the time and that more than 75% of the alterations had potentially important clinical consequences. 30 Nurses can resist serving as untrained, ad hoc interpreters or, if in a facility that expects dual-role interpreters, can advocate for validation of continued competency among interpreters.…”
Section: Limited English Proficiencymentioning
confidence: 99%
“…29 Evaluation of communications between patients' families and health care providers during interpreted conferences revealed that alterations occurred 55% of the time and that more than 75% of the alterations had potentially important clinical consequences. 30 Nurses can resist serving as untrained, ad hoc interpreters or, if in a facility that expects dual-role interpreters, can advocate for validation of continued competency among interpreters.…”
Section: Limited English Proficiencymentioning
confidence: 99%
“…17,20,31,32 Other situations in the pediatric inpatient setting that may benefi t from an FCC include: a prolonged hospital stay, involvement of several consulting physicians, preparation for discharge, or a particularly confusing diagnosis. We propose a model for the FCC on the pediatric inpatient service that is fl exible enough to allow for conferences with a variety of goals (Fig 1).…”
Section: Why Do We Have Inpatient Fccs?mentioning
confidence: 99%
“…Even with interpretation services, 1 study found less information is transmitted in interpreted conferences compared with English-only conferences. 32 Research on family-centered rounds indicates that families prefer to have bilingual physicians caring for them, and if they are not available, they prefer in-person versus telephone translators. 33 The availability of professional interpreters may be limited, 34 and pediatricians often resort to ad hoc interpreters, despite the legal, ethical, and quality concerns of this option.…”
Section: Family Advocacymentioning
confidence: 99%
“…25,39,41 Families who do not speak English are especially at risk for inadequate anticipatory guidance, owing to poor communication between the family and team. [42][43][44] When families are being asked to make decisions that will impact the quality and length of their child' s life, it is part of the physician' s ethical duty to provide timely information and a pathway toward shared decision-making for the family. Physicians must support and respect families' needs to make decisions that will be best for their individual child, but they should not leave the family completely alone to make these difficult decisions.…”
Section: Enhancing Shared Decision-makingmentioning
confidence: 99%